Implementasi Metode Double Exponential Smoothing untuk Prediksi Jumlah Kebutuhan Air di PDAM Tirta Mon Pase - Rahmatin Nisak; Arnawan Hasibuan; Said Fadlan Anshari; Rozzi Kesuma Dinata; Fadlisyah Fadlisyah (Universitas Al Azhar Indonesia, 2026)
Clean water is an essential human need, yet its provision is frequently disrupted by demand uncertainty, as experienced by PDAM Tirta Mon Pase with recurring public complaints regarding water supply interruptions. This study aims to design and implement a water demand forecasting system using the Double Exponential Smoothing (Holt’s Linear Trend) method and to evaluate its accuracy. The research utilized monthly historical water production data from January 2022 to December 2024 (36 observations) obtained from PDAM Tirta Mon Pase. The model was applied with smoothing parameters α = 0.8 and β = 0.2, and accuracy was measured using Mean Absolute Percentage Error (MAPE). The results show a very high level of accuracy with an overall MAPE of 3.56% (2022: 4.18%; 2023: 3.91%; 2024: 2.65%), and the forecast predicts water demand in December 2027 will reach 1,131,071.39 m³. It can be concluded that the Double Exponential Smoothing method is highly accurate and effective for forecasting water demand at PDAM Tirta Mon Pase. The developed system is therefore strongly recommended for operational adoption as a strategic decision-support tool in water resource planning, production, and infrastructure development.